The Effectiveness of Time Perspective Training on Academic Burnout, Self-Defeating Behavior, and Thought Control Strategies in Upper Secondary School Students - Seifi, Saeb; Jahan, Faezeh; Sotoudeh, Nemat; Rezaei, Noor Mohammad (KMAN Counseling & Psychology Nexus, 2026)
This study aimed to examine the effectiveness of time perspective training on reducing academic burnout and self-defeating behavior and on improving thought control strategies among upper secondary school students. The study employed a quasi-experimental design with pretest, posttest, and follow-up assessments and a control group. Participants were 45 upper secondary school female students selected through purposive sampling and randomly assigned to experimental and control groups. The experimental group received a structured time perspective training program based on Zimbardo’s theoretical framework delivered in 10 sessions over 8 weeks, while the control group received no intervention. Data were collected using the Academic Burnout Questionnaire, the Self-Defeating Behavior and Cognition Scale, and the Thought Control Questionnaire. Statistical analyses were conducted using univariate and multivariate analysis of covariance, with Bonferroni post hoc comparisons. After controlling for pretest scores, significant group effects were observed for academic burnout (F = 316.32, p < .001, η² = .556), self-defeating behavior (F = 34.20, p < .001, η² = .430), and thought control strategies (F = 79.55, p < .001, η² = .369). Bonferroni comparisons indicated that the experimental group demonstrated significantly lower levels of academic burnout and self-defeating behavior and significantly higher adaptive thought control at posttest compared with the control group (p < .001). These effects remained stable at follow-up. Time perspective training constitutes a highly effective intervention for improving academic and psychological functioning in adolescents and offers a promising approach for school-based mental health and educational support programs.